(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Increased attention to corporate governance with the increasing need for investors and other parties in the Iraqi market for securities of the information credible and confidence and greater transparency in the disclosure as well as the systems of governance lead to raise the value of the company and that by reducing the cost of capital and reduce the cost of financing, as well as that there are indications modern measurement can be adopted by the Iraqi market for securities for the purpose of evaluating the performance of listed companies and then raise their value. The research problem is that there is no framework or structure of the legal and local rules for the application of corporate governance in Iraq obliges listed companies which applied as well as that of the Iraqi market for securities depends style financial analysis of the traditional evaluation of the performance of listed companies and the failure to adopt indicators modern and built on the basis of value. The research aims to develop a proposal for a specimen guide corporate governance to strengthen the companies’ efforts to improve its financial performance . And the application of financial performance metrics on the basis of value creation . For the purpose of addressing the problem of the lack of a window or a legal structure and local rules for the application of corporate governance in Iraq require companies to contribute to its implementation , which is reflected in the breach in the levels of financial performance and achieve the desired goals and the mouthpiece of the financial performance, based on the value in order to protect companies and stakeholders , capital and all parties dealing with the company as well as that of the Iraqi market for securities depends style financial analysis of the traditional evaluation of the performance of listed companies and the failure to adopt indicators modern and built on the basis of value and thus raise the level of the economy in Iraq , and the adoption of existing investors and prospective on these indicators in the investment and the purchase of shares of these companies .